Research on Turning Deformation After Heat Treatment to Aviation Gears with Thin Webs Considering Multi-physics Coupling Effects - Tang Cheng; Tang Zhongwei; Tao Qi; Tang Jinyuan (Jixie chuandong)
Gears with a thin web are often used in aerospace occasions because it has many advantages, such as low-weight and structure-load matching. However, due to the small rigidity and the complex process with the multiple physics, such as stress field and temperature field, it is difficult to accurately control and predict the deformation and machining accuracy. In this study, taking the heat treatment and turning process of the gear with thin web as the research object, the mapping model between the process parameters and its stress field is established, and the correctness of the model is verified by experiments. Based on this model, the effects of different process parameters, routing and clamping methods on the deformation in the heat treatment and turning process of the aviation gear with thin webs are analyzed, and the main factors leading to the deformation of parts are defined and optimized.